Emerging trends and research foci of oncolytic virotherapy for central nervous system tumors: A bibliometric study - Cheng, Kunming; Zhang, Huan; Guo, Qiang; Zhai, Pengfei; Zhou, Yan; Yang, Weiguang; Wang, Yulin; Lu, Yanqiu; Shen, Zefeng; Wu, Haiyang (Frontiers in Immunology, 2022)
Background: Central nervous system tumor (CNST) is one of the most complicated and lethal forms of human tumors with very limited treatment options. In recent years, growing evidence indicates that oncolytic virotherapy (OVT) has emerged as a promising therapeutic strategy for CNSTs. And a considerable amount of literature on OVT-CNSTs has been published. However, there are still no studies summarizing the global research trends and hotspots of this field through a bibliometric approach. To fulfill this knowledge gap, bibliometric analysis was conducted based on all publications relating to OVT-CNSTs since 2000s. Methods: We searched the Web of Science Core Collection for all relevant studies published between 2000 and 2022. Four different tools (online analysis platform, R-bibliometrix, CiteSpace and VOSviewer) were used to perform bibliometric analysis and network visualization, including annual publication output, active journals, contribution of countries, institutions, and authors, references, as well as keywords. Results: A total of 473 articles and reviews were included. The annual number of publications on OVT-CNSTs showed a significant increasing trend. Molecular Therapy and Cancer Research were the most active and co-cited journals, respectively. In terms of contributions, there is no doubt that the United States occupied a leading position with the most publications and the highest H-index. The institution and author that contributed the largest number of publications were Ohio State University and Chiocca EA, respectively. As can be seen from citation analysis, the current studies mainly focused on preclinical and phase I/II clinical results of various oncolytic virus for CNSTs treatment. Keywords co-occurrence and burst analysis revealed that the following research topics including immunotherapy, T-cells, tumor microenvironment, vaccine, blood-brain-barrier, checkpoint inhibitors, macrophage, stem cell, and recurrent glioblastoma have been research frontiers of this field and also have great potential to continue to be research hotspots in the future. Conclusion: There has been increasing attention on oncolytic viruses for use as CNSTs therapeutics. Oncolytic immunotherapy is a topic of great concern in this field. This bibliometric study provides a comprehensive analysis of the knowledge base, research hotspots, development perspective in the field of OVT-CNSTs.